Diversity of plant as a complementary to the staple food of dawanese east nusa tenggara - Hanas, Dicky Frengky; Bria, Emilia Juliyanti; Bano, Elinora Naikteas (STKIP Persada Khatulistiwa Sintang, 2024)
The Dawanese have a staple food which is also a typical food, namely bose and katemak, the manufacture of which utilizes a variety of cereal plant resources and is generally served with a complement in the form of local vegetables or typical chili sauce of the Dawan people. This study aims to determine the types of plants used by the Dawan community as a complement to staple food. Exploration methods and interviews were conducted to obtain information on the names of species and plant parts used. The plant data obtained were identified and then analyzed descriptively. The results showed that there were 12 types of plants from the Solanaceae, Rutaceae, Apiaceae, Lamiaceae, Amaryllidaceae, and Alliaceae families which were generally used in the manufacture of chili sauce typical of the Dawan community. The plant parts used are leaves, fruit, and tubers. Knowledge about plant utilization needs to be accompanied by knowledge about plant preservation and conservation efforts.